The Relationship Between Thermal Performance, Thermal Comfort And Occupants. A Study Of Thermal Indoor Environment In Selected Students Accommodation In Universiti Sains Malaysia (USM), Penang. - R S Wafi, Sulaiman; Ismail, Mohd Rodzi (2008)

(untitled)
Thermal comfort is considered to be a principal requirement that is usually demanded of by occupants of accommodation units.